Alternative Consumer Cooperatives - Oba, Beyza; Özsoy, Zeynep; Teufer, Birgit (Taylor and Francis, 2025)
As defined by Consumer Co-operatives Worldwide (CCW), which represents 26 national organizations of consumer cooperatives around the world, “a consumer cooperative is an autonomous association of consumers united voluntarily to meet their common economic, social and cultural needs and aspirations through a jointly owned and democratically controlled enterprise”. In other words, a consumer cooperative is an enterprise that is owned by consumers who unite voluntarily to fulfill their common needs and aspirations. Like in the case of food cooperatives, cooperatives that own retail outlets run by consumers are the most common type of consumer cooperatives. However, there are also consumer cooperatives operating in areas such as childcare, health care, insurance, housing, utilities, and personal finance. The main purpose of a consumer cooperative is not to maximize profit but to provide quality products and services at the lowest price to the customers. © 2026 selection and editorial matter, Lewis Akenji, Philip J. Vergragt, Halina Szejnwald Brown, Thomas S.J. Smith and Laura Maria Wallnöfer; individual chapters, the contributors
Keywords: Health-Care Insurance; Lowest Price; Product And Services; Quality Product; Quality Services; Retail Outlets